Stiffening of Circumferential F-Actin Bands Correlates With Regenerative Failure and May Act as a Biomechanical Brake in the Mammalian Inner Ear - Rudolf, Mark A.; Andreeva, Anna; Kim, Christina E.; DeNovio, Anthony C.-J.; Koshar, Antoan N.; Baker, Wendy; Cartagena-Rivera, Alexander X.; Corwin, Jeffrey T. (Frontiers in Cellular Neuroscience, 2022)
The loss of inner ear hair cells causes permanent hearing and balance deficits in humans and other mammals, but non-mammals recover after supporting cells (SCs) divide and replace hair cells. The proliferative capacity of mammalian SCs declines as exceptionally thick circumferential F-actin bands develop at their adherens junctions. We hypothesized that the reinforced junctions were limiting regenerative responses of mammalian SCs by impeding changes in cell shape and epithelial tension. Using micropipette aspiration and atomic force microscopy, we measured mechanical properties of utricles from mice and chickens. Our data show that the epithelial surface of the mouse utricle stiffens significantly during postnatal maturation. This stiffening correlates with and is dependent on the postnatal accumulation of F-actin and the cross-linker Alpha-Actinin-4 at SC-SC junctions. In chicken utricles, where SCs lack junctional reinforcement, the epithelial surface remains compliant. There, SCs undergo oriented cell divisions and their apical surfaces progressively elongate throughout development, consistent with anisotropic intraepithelial tension. In chicken utricles, inhibition of actomyosin contractility led to drastic SC shape change and epithelial buckling, but neither occurred in mouse utricles. These findings suggest that species differences in the capacity for hair cell regeneration may be attributable in part to the differences in the stiffness and contractility of the actin cytoskeletal elements that reinforce adherens junctions and participate in regulation of the cell cycle.